Comprehensive Analysis Of Income Tax Article 23 Based On Literacy In Various Companies In Indonesia - Ahmad Fais El Wajdi; Anggara Ramadhansyah; Devi Liana; Khairunnisa Agustin; Rizki Purwanti; Galih Supraja (International Journal of Economic Research and Financial Accounting, 2025)
Income Tax Article 23 (PPh 23) is one of the important instruments in the Indonesian taxation system that  targets deductions on income from capital, services, or gifts and awards. This study aims to review the  implementation, calculation, recording, and reporting of PPh 23 based on studies that have been conducted in  various companies such as PT Semara Perkasa Lestari, PT Store Sent e-Logistik Indonesia, Perum Bulog, PT Grin Kar Indonesia, and PT Perkebunan Nusantara Enam. The method used is a literature study of relevant journals, tax regulations such as Government Regulation No. 36 of 2008, and the practice of implementing e-Bupot Unification. The results of this study indicate significant challenges in terms of compliance, technical  mastery of calculations, and adaptation to electronic reporting systems. This study recommends increasing  socialization and training for business actors and optimizing the e-Bupot system. This study is expected to be a reference for academics, tax practitioners, and taxpayers in understanding and implementing PPh Article 23  more appropriately and efficiently.